Investigation on carrier recombination and energetics of kesterite materials for photovoltaic applications - Zeng, Xin (2016)
Cu2ZnSnS4-xSex (CZTSSe) based kesterite solar cells, comprise of abundantly available and environmental benign elements, which have drawn widespread attention as they are excellent candidatesfor thin film solar cells. In addition, other advantageous qualities of CZTSSe that makes it suitable for thin film applications include its high absorption coefficient in the visible wavelength range, intrinsic ptype conductivity and a direct band gap. The technologies available to fabricate high quality CZTSSe absorbers are still in their infancy, with the solution based techniques requiring either a highly toxic and dangerous solvent such as hydrazine, or an organic solvent such as methanol. Thus, an environmentally green and cost effective method is in current high demand. In this work, an aqueous-based chemical spray pyrolysis technique was used to deposit a uniform CZTS layer on Mo coated glass. The film was further processed in a high temperature selenization furnace to obtain a highly crystalline CZTSSe absorber. Using X-ray diffraction (XRD) and Raman spectroscopy, no detectable secondary phase was observed from the CZTSSe absorbers. A uniform elemental distribution was suggested from SIMS depth profiling, except for slightly increased concentrations of Zn and S close to the Mo contact layer. The S/Se ratio can be tuned by applying different amounts of Se in the selenization process, which resulted in similar solar cell conversion efficiencies above 5%. The highest efficiency obtained after process optimization was 7.5%, which to the best of our knowledge, is the highest efficiency obtained for a kesterite containing solar cell fabricated by an aqueous-based solution method.